FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN MANUFAKTUR - Rinaldy Wiyadi; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to determine the impact of profitability, leverage, firm size, firm growth, and dividend policy on firm value. This research uses data from manufacturers listed on the Indonesia Stock Exchange from 2016 to 2019. The samplewas selected using purposive and 46 companies. The data was processed by Eviews 10. The results of this show that leverage has a significant positive impact on firm value. Firm size of the company has a negative impact on the value of the company. Profitability, firm growth and dividend policy do not have a significant impact on firm value.